The development of a reading model in physics teaching for argumentation skills and critical thinking skills: a ‘Fuzzy Delphi’ method - Siswanto, Siswanto; Subali, Bambang; Hartono, Hartono; Masturi, Masturi; Wibowo, Firmanul Catur; Trisnowati, Eli; Haryati, Sri; Sukarno, Sukarno (Journal of Turkish Science Education, 2025)
Reading activities are essential to the physics learning process. Physics teaching has mostly been carried out to foster higher order thinking skills such as critical thinking and argumentation skills. This present study aims to develop a reading model that can be enacted in physics education to facilitate critical thinking and argumentation skills. This study employed the Fuzzy Delphi method. In this study, the Fuzzy Delphi method was divided into two phases. In the first phase, the experts (5 experts) were interviewed to determine the relevance of reading activities to the development of argumentation and critical thinking skills in the physics learning process. Then, in the second phase, we employed 27 experts to determine the stages of the reading model. In this phase, a questionnaire was developed consisting of fourteen questions. The research findings indicate that a consensus was reached on the stages of the reading model aimed at developing argumentation and critical thinking skills. These stages include predicting the purpose and content of the passage, explaining phenomena, reading by critical-argumentation activities, and evaluating predictions of the purpose, content, and explanation of the phenomena.